Electrochemical investigation of polyaniline functionalized graphene as oxygen evolution reaction (oer) electrode - Heidi, Tan Hui Yi (2025)
This study explores the synthesis and electrochemical performance of polyaniline reduced graphene oxide (PANI-rGO) as a high-performance electrocatalyst for the oxygen evolution reaction (OER). To enhance the catalytic activity of graphene, we employed the in-situ polymerizing polyaniline (PANI) on the graphene surface to effectively introduce nitrogen functionalities. Comprehensive characterization using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Ultraviolet-Visible (UV-Vis) Spectroscopy confirmed the successful synthesis of the Polyaniline-Reduced Graphene Oxide (PANI-rGO) composite, which exhibited a well-defined morphology and enhanced surface area. Electrochemical investigations, including Linear Sweep Voltammetry (LSV), Electrochemical Impedance Spectroscopy (EIS), and Cyclic Voltammetry (CV), demonstrated that the PANI-rGO electrode exhibited superior OER activity compared to pristine Reduced Graphene Oxide (rGO) and bare glassy carbon electrodes, achieving a higher current density at a lower overpotential. This enhanced performance is attributed to the synergistic effects of PANI incorporation, which significantly improved charge transfer kinetics, reduced solution resistance, and increased the number of active sites for OER. The findings of this study highlight the potential of PANI-rGO as a promising, cost-effective, and high-performance electrocatalyst for sustainable energy applications, paving the way for the development of advanced energy conversion and storage technologies.